Clinical implications of idiopathic pulmonary fibrosis and lung cancer - Hongseok Yoo; Man Pyo Chung (Precision and Future Medicine)
Idiopathic pulmonary fibrosis (IPF) is characterized by chronic progressive fibrosis of the lungs of unknown etiology. The prognosis of IPF is poor, with a median survival of 3 to 5 years. Lung cancer is one of the most frequently associated comorbidities of IPF, often resulting in grave outcomes. Patients with IPF have a higher risk for lung cancer than the general population. Lung cancer frequently develops in older male IPF patients with smoking history. Squamous cell carcinoma is the most common histological type, followed by adenocarcinoma. Such cancers typically develop abutting or within fibrosis. One of the major obstacles in making therapeutic decisions for these patients is the complications after treatment and subsequent poor prognosis. Numerous studies have reported post-treatment complications, such as acute exacerbation of IPF, pneumonia, and persistent air leakage, and their impact on survival. Higher mortality rates have consistently been reported among patients diagnosed with both IPF and lung cancer compared to those with either IPF or lung cancer alone. Thorough risk assessment for complications, selection of appropriate therapeutic modality, and use of antifibrotic agents, such as pirfenidone or nintedanib, may help prevent complications and improve survival. Nevertheless, further research is necessary to establish optimal treatment strategies for patients diagnosed with IPF and lung cancer.